Effect of Telehealth Implementation on Outpatient Anxiety Level - Eni Nuraeni (CV. Get Press Indonesia, 2026)
Anxiety in outpatients is a psychological problem that often arises due to long lines, limited consultation time, and concerns about diagnosis and therapy. The use of telehealth as a technology-based health service innovation has the potential to improve patient access, efficiency, and comfort so that it can reduce anxiety levels. However, the scientific evidence regarding the effectiveness of telehealth on outpatient anxiety in Indonesia is still limited. This study aims to analyze the effect of the application of telehealth on the level of anxiety of outpatients in Dr. Hasan Sadikin Bandung. This study used a quasi-experimental design with one group pretest-posttest approach without a control group. A sample of 80 outpatients were selected using acidental sampling technique according to inclusion and exclusion criteria. Interventions in the form of telehealth services are provided during scheduled consultation periods. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) instrument before and after the intervention. Data analysis was conducted using paired t-test to determine the difference in the average anxiety score before and after the application of telehealth with a significance level of p<0.05. The results showed that the average anxiety score before the intervention was 25.1 ± 5.4 and decreased to 16.2 ° 4.9 after the implementation of telehealth. The paired t-test results showed a statistically significant difference (p=0.000), with an average decrease of 8.9 points. It was concluded that the application of telehealth has a significant effect in reducing the level of outpatient anxiety. Operational implications of this study is the need for optimization of telehealth services as part of outpatient service standards to support the comfort and psychological stability of patients.